PRE-QUESTIONING TECHNIQUE TO TEACH READING COMPREHENSION FOR VOCATIONAL SCHOOL LEVEL (RETAIN, 2013)
Abstrak Di Indonesia, bahasa Inggris dianggap sebagai bahasa asing pertama. Ada empat macam keterampilan dalam bahasa Inggris yang harus dikuasai oleh murid-murid yang belajar bahasa Inggris, yaitu : mendengarkan, membaca, dan menulis. Diantara keempat keterampilan berbahasa Inggris, keterampilan membaca dianggap sebagai salah satu hal yang paling penting dalam pembelajaran bahasa. Keterampilan membaca menjadi satu bagian  dalam keterampilan berbahasa yang harus dikuasai oleh pelajar karena keterampilan membaca mempunyai sebuah peranan penting dalam bidang pendidikan. Membaca merupakan sebuah jembatan bagi murid-murid untuk mendapatkan informasi yang diperlukan di bidang pendidikan, seperti mentransfer informasi dan ilmu dari buku-buku paket atau panduan. Mengingat pentingnya keterampilan membaca untuk murid-murid, kreatifitas guru dibutuhkan dalam pemilihan teknik pembelajaran untuk pelajaran reading. Hal ini merupakan peranan guru untuk dapat menciptakan lingkungan kelas yang menyenangkan dan membangun minat dan motivasi murid-murid dalam pelajaran membaca dalam bahasa Inggris. Dalam pembelajaran membaca dalam bahasa Inggris, hal yang paling penting adalah pemahaman murid-murid terhadap teks bacaan untuk dapat menangkap makna/maksud penulis. Untuk dapat memahami sebuah teks bacaan, sebuah teknik yang tepat untuk mengajar reading sangatlah penting. Sehingga, seorang guru bahasa Inggris harus kreatif dalam memilih teknik pengajaran reading yang tepat. Salah satu teknik alternatif yang digunakan untuk menngajar reading adalah pre-questioning technique. Pre-questioning technique di definisikan sebagai beberapa pertanyaaan yang akan diberikan pada murid-murid sebelum kegiatan pembelajaran bahasa Inggris, sebelum murid-murid membaca seluruh teks bacaan, untuk membangun minat dan motivasi murid-murid. Dengan memberikan beberapa pertanyaaan sehubungan dengan topik bacaan yang akan diberikan, diharapkan dapat membantu murid-murid untuk dapat memahami bacaan lebih baik karena sebelum mereka diminta untuk membaca teks, mereka dapat menebak atau memprediksi isi dari teks bacaan melalui beberapa pertanyaan yang berhubungan dengan topik yang diberikan pada mereka sebelum mereka membaca teks bacaan. Dalam studi ini, peneliti mencoba untuk meneliti penerapan teknik pre-questioning pada kelas bahasa Inggris kelas Sekolah Menengah Kejuruan, Akuntansi, dan bagaimana untuk mengetahui bagaimana kemampuan murid-murid setelah penerapan teknik pre-questioning. Dalam studi ini, peneliti menggunakan metode penelitian deskriptif kuantitatif dengan non partisipasi peneliti. Dalam melaksanakan penelitian ini, Abstract   In Indonesia, english is considered as the first foreign language. There are four skills that should be mastered by the English learners, they are: listening, speaking, reading, and writing. Among those four skills, reading is one of the most important skills in learning language. Reading skill becomes a part of language skill that the students have to master since reading skill has an important role in education field. Reading is a bridge for the students to get the information needed in their education field, such as trasferring information and knowledge from textbooks. Considering the importance of reading for the students, teacher’s creativity is needed to select the appropriate technique in teaching reading comprehension. It is the teacher’s role to create enjoyable classroom environment and build up students’ interest and motivation in learning reading. In learning reading, the most important point is students’ comprehension toward the text in order to get the author’s messages. In order to comprehend a text, an appropriate technique to teach reading is important. So that, an English teacher should be creative in selecting the technique to teach reading. One of  the alternative techniques used to teach reading is pre-questioning technique. Pre-questioning technique is defined as some questions provided before the students read the whole text, in order to build the students’ interest and motivation. By giving some questions related to the theme of the text given, it is expected to help the students comprehend the text better since before they are asked to read the text, they can predict the content of the text through some related questions given before they read the text. In this study, the researcher tries to observe how is the implementation of pre-questioning technique to the English class of vocational school level, and how is the students’ ability after the implementation of pre-questioning technique. In this study, the researcher uses descriptive quantitative research with non-participant researcher. In conducting this study, the researcher collected the data by observing both the teacher and the students’ activities during the implementation of pre-questioning technique. The subjects of this study are the English teacher and the first grade students of accounting class of SMK Pawiyatan Surabaya. The result of this study showed that by applying the Implementation of pre-questioning technique, the students can understand the text well. To know the students’ ability after the implementation of pre-questioning technique, the teacher used exercises in form of short-answer questions or W-H questions and True of False completion. The result of the students’ achievement are analyzed based on Heaton’s way and show “Good” classification. From this result showed, finally the researcher can conclude that the implementation of pre-questioning technique to teach reading comprehension is successful.   Key words: pre-questioning, technique, teaching reading, reading comprehension